Reframing research relationships: How participatory video helped us rethink farmer participation - 1000FARMS Platform; Muller, Anna (2025)
This knowledge brief shares how the team lead by Anna Muller and partners used participatory video as an innovative tool to shift the dynamics of on-farm tricot trials, from extractive data collection toward more meaningful collaboration with farmers. In Rwanda, Nigeria, and Uganda, over 25 farmers and researchers were trained to co-produce community videos, enabling participants to express their experiences, values, and perspectives in their own words and images. The initiative helped surface insights not usually captured in surveys, such as social dynamics, motivations, and aspirations, and fostered a sense of pride and ownership among farmers. The process also helped CGIAR researchers reflect on what participation means in citizen science and how methods like participatory video can enhance trust, inclusion, and mutual learning in farmer-led innovation.